2015
DOI: 10.4103/0974-1208.170410
|View full text |Cite
|
Sign up to set email alerts
|

Novel FSH receptor mutation in a case of spontaneous ovarian hyperstimulation syndrome with successful pregnancy outcome

Abstract: The objective is to study the FSH receptor (FSHR) for mutations in a case of spontaneous ovarian hyperstimulation syndrome (sOHSS). This is a single case study and it examined patient who presented with spontaneous critical OHSS in early pregnancy and had successful good obstetric outcome. Intervention of this study was analysis of blood for genetic analysis of FSHR postdelivery. The main outcome measure noted was FSHR mutation. The study resulted in a novel, here though unreported, heterozygous mutation in FS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 17 publications
(20 reference statements)
0
3
0
1
Order By: Relevance
“…There are a few known mutations, in all domains of FSHR, which produce a spontaneous ovarian hyperstimulation syndrome (with elevated E2, polycystic ovaries), mostly described during pregnancy. The mutated FSHR displays an increased responsiveness to the physiologically high serum level of hCG during the first trimester of pregnancy (11,12). These mutations (eg FSHR D567N, T449A, T449I, S128T) induce an expansion of the receptor's specificity, named promiscuous activation, with hypersensitivity to elevated hCG and TSH levels (2).…”
Section: Activating Fshr Mutations In Womenmentioning
confidence: 99%
“…There are a few known mutations, in all domains of FSHR, which produce a spontaneous ovarian hyperstimulation syndrome (with elevated E2, polycystic ovaries), mostly described during pregnancy. The mutated FSHR displays an increased responsiveness to the physiologically high serum level of hCG during the first trimester of pregnancy (11,12). These mutations (eg FSHR D567N, T449A, T449I, S128T) induce an expansion of the receptor's specificity, named promiscuous activation, with hypersensitivity to elevated hCG and TSH levels (2).…”
Section: Activating Fshr Mutations In Womenmentioning
confidence: 99%
“…Ebben az esetben az endogén hCG is liganddá válhat az FSH-receptor számára [20]. Számos publikáció írt le spontán fogant terhesség kapcsán, akár visszatérően is jelentkező, súlyos fokú OHSS-t ilyen jellegű mutációk esetén [21][22][23]. Az FSH-receptor expresszióját negatív irányba szabályozó egyéb fehérjék, például a BMP15 (bone morphogenetic protein 15) csökkent működését okozó mutációja szintén növeli az OHSS kialakulásának kockázatát [24].…”
Section: Kórélettanunclassified
“…Mutant FSHRs with increased sensitivity to glycoprotein hormones and enhanced basal activity were described in OHSS patients [ 27 , 32 36 ]. These mutations fall within the transmembrane helices [ 27 , 33 , 35 , 37 ], in the extracellular domain [ 36 , 38 ] and in the cytoplasmic tail [ 39 , 40 ] of the receptor, impacting the FSHR density in the cell surface and the activation of intracellular signaling pathways. More recently, a study found that two biallelic heterozygous FSHR mutations were linked to OHSS in a pregnant patient affected by sOHSS, triggered by hCG [ 22 ].…”
Section: Introductionmentioning
confidence: 99%